Consumption patterns of women graduates in the district of Perak Tengah - Mustafa, Norazah; Mat Isa, Azizah; Aw, Yang Huey (2011)
The research was undertaken to look at the spending patterns of women graduates who were residents in Perak Tengah. The study focused on women graduates in the government sectors and took into consideration the similarities and differences of consumption patterns between single and married women. This study involved 300 respondents. They were chosen by stratified sampling technique. An inferential statistics of t-test was used to analyze the data. This study revealed that the spending patterns of women graduates in Perak Tengah are similar to the survey made at the national level and selected countries such as Australia and New Zealand. The focus on the spending is still on the basic needs (foods, shelter and transport). In deciding to purchase a household item, the study also revealed that the respondents are influenced by their family members, quality and price of the product. It is recommended that further studies on spending patterns to be conducted for both men and women in Perak Tengah. Such studies could also be extended to spending patterns of students in specific places in Perak Tengah such as Bandar Seri Iskandar, Bandar Universiti and Bota.